Pemanfaatan Media Youtube Oleh David Wewe Official Dalam Upaya Meningkatkan Kesadaran Hukum Masyarakat Kota Padang - Ulfa Zakiyyah; Dion Eriend (CV. ITTC INDONESIA, 2026)
This research is motivated by the rapid development of information technology in the Industrial Revolution 4.0 era, which has transformed social interaction patterns into digital-based ones, where social media platforms like YouTube have become crucial tools for modern public education. In this context, the David Wewe Official YouTube channel has emerged as a communication phenomenon that utilizes law enforcement content to provide legal information to the public. This descriptive qualitative study aims to describe the utilization of the channel in efforts to increase legal awareness among the people of Padang City, using data collection techniques such as in-depth interviews, field observations, and documentation. The results show that the David Wewe Official YouTube channel has effectively served as a bridge for legal information by implementing the interactive and accessible characteristics of New Media. The use of content that showcases both the humanistic side and the firmness of the police force has successfully built public trust and encouraged audiences to be more law-abiding. Furthermore, the media convergence strategy—achieved by integrating content across Instagram and TikTok platforms—has proven to expand the reach of legal education. Overall, the active engagement of the Padang City community and viewers in the comments section indicates an internalization of the legal messages conveyed, demonstrating that this platform serves not only as entertainment but also as an important instrument in improving the legal literacy of Padang City residents.